PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK MAKE A MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SITIUNG KABUPATEN DHARMASRAYA TAHUN PELAJARAN 2013-2014 - Kurnia Putri, Fenny; Longgom. Nst, Minora; febriana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The research was appeared because of an understanding of mathematical concepts students are still low. The research aims to determine which one is better technique will be implemented to the students of class VIII, SMP N 1 Sitiung in theÂ academic period of 2013/2014. The alternative techniques are make a match technique or conventional technique. The type of this research is a random design experiment to subject. The population is all of student from class VII in SMPN 1 Sitiung that has registered in the academic period of 2013-2014. The sample of the research is class of VIIID as experiment class and class of VIIIF as the control class. The instrument of the research is the last with a score of realibility is 0,795. Based of the result data analysis found that the average student learning outcomes in experiment class is 74,99 and the outcome is higherÂ than outcome from control class that is 38,24. Data is analyzed with t-test that obtained tcount = 10,90 and ttable = 1,67. The hypothesis can be accepted. So, it can be concluded that studentâs understanding of mathematical concepts using cooperative learning model is better than conventional technique in class VIII, SMPN 1 Sitiung.Â